Emotional Closeness Among NICU Fathers: A Qualitative Descriptive Study. (February 2022) - Lebel, Valérie; Feeley, Nancy; Gosselin, Émilie; Axelin, Anna
Abstract : Background: The unique perspective of fathers with an infant in the neonatal unit on the development of emotional closeness toward their infant is not well understood. The purpose of this study is to explore experiences and instances of emotional closeness from the perspective of fathers as well as factors influencing emotional closeness during an infant's hospitalization in the neonatal unit. Methods: This qualitative descriptive study employed one-on-one interviews with fathers recruited in a level 3 neonatal unit. The interview data were analyzed with thematic analysis, and emerging themes and subthemes were organized according to dimensional analysis. Results: Eight fathers agreed to take part in this study. According to the participants, emotional closeness was a complex process composed of multiple dimensions. More specifically, emotional closeness was a difficult-to-describe, mixed, and growing feeling influenced by multiple factors such as the environment, co-parenting, and the father–infant relationship. It occurred in the contexts of presence and separation in the neonatal unit and was part of the development of the father–infant relationship. Implications for Practice: The results presented in this article are important for neonatal intensive care unit nurses who support fathers in the development of their fathering role. By knowing more about the process and dimensions of emotional closeness, nurses can direct their interventions with fathers to enhance emotional closeness and better understand their experience. Implications for Research: No previous study has addressed emotional closeness as a complex process with multiple components like the current study. These findings contribute to our understanding of the process of emotional closeness for fathers.